1980
DOI: 10.1002/jbm.820140308
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric ceramic implants: A feasibility study

Abstract: A piezoelectric ceramic has been investigated as a direct substitute for hard tissues. Barium titanate (BaTiOz) power was slipcast and fired at 1430 degrees C for 2 hr, then made piezoelectric by polarizing. After 16 and 86 days of implantation in the cortex of the femoral midshafts, the femora with test specimens were sectioned into about 4-cm lengths. Their voltage outputs were measured under cyclic load at 1 Hz. The present results show that the voltage gradient at the implant surface is 0.15 mV/mm for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…To this purpose, in vivo conditions are highly suitable, as a natural load is continuously applied to the implanted material, thus exerting its piezoelectric characteristics. Several experiments were carried out, implanting piezoelectric BaTiO 3 , polyvinylidene fluoride (PVDF), HABT, and [P(VDF-TrFE)-BaTiO 3 ] inside canine femora, as well as inside rat and rabbit tibiae [59][60][61][62]. Results clearly showed that the piezoelectric nature of the poled and mechanically loaded materials contributed to the improvement of biological responses.…”
Section: Bone Tissue Engineeringmentioning
confidence: 95%
“…To this purpose, in vivo conditions are highly suitable, as a natural load is continuously applied to the implanted material, thus exerting its piezoelectric characteristics. Several experiments were carried out, implanting piezoelectric BaTiO 3 , polyvinylidene fluoride (PVDF), HABT, and [P(VDF-TrFE)-BaTiO 3 ] inside canine femora, as well as inside rat and rabbit tibiae [59][60][61][62]. Results clearly showed that the piezoelectric nature of the poled and mechanically loaded materials contributed to the improvement of biological responses.…”
Section: Bone Tissue Engineeringmentioning
confidence: 95%
“…In agreement with earlier work, increased ossification was found on piezoelectric films made from PLLA in a rabbit model. 50 A further study showing an improved biological response to piezoelectric materials was carried out by Feng et al 12 As with the earlier studies, 44,45 BaTiO 3 -containing ceramics were implanted in canine subjects. In this case, the piezoelectric material was in the form of a hydroxyapatite-barium titanate (HABT) composite.…”
Section: In Vivo Studiesmentioning
confidence: 97%
“…45 Ceramic samples with porous surfaces and a voltage coefficient (g 33 ) of approximately 9 9 10 À3 mVN À1 were implanted into canine femora (specifically, into the cortex of the femoral midshaft). The g 33 coefficient is a measure of electric field generated per unit stress.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Their first application to the biomaterials area was with the discovery of lead-free piezoelectric ceramic barium titanate (BaTiO 3 ) (Park et al, 1980). Lithium sodium potassium niobate has broadened the scope of lead-free piezoelectric ceramics owing to its better and more stable piezoelectricity than barium titanate (Saito et al, 2004).…”
Section: Discussionmentioning
confidence: 99%